The Role of Zakat, Economic Growth, and Human Resource Quality In Indonesian Inequality - Yanti, Dharma; Mahamood , Siti Fatahiyah (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2025)
This study investigates the partial and simultaneous influence of Zakat, Infaq, and Sadaqah (ZIS), economic growth, and human resource quality on income inequality in Indonesia from 2013 to 2023. Addressing the research gap in prior studies that typically examined these factors in isolation, this research employs a quantitative approach using multiple linear regression analysis to evaluate annual time-series data. The independent variables include ZIS distribution, economic growth, and the Human Development Index (HDI), while the dependent variable is the Gini index. The findings reveal that individually, none of the three variables significantly affect income inequality. However, when assessed simultaneously, they exhibit a statistically significant impact, suggesting a complementary role in reducing inequality. ZIS and HDI display a negative correlation with inequality, indicating potential in mitigating disparities, while economic growth correlates positively. These results imply that zakat alone is insufficient and must be integrated with inclusive economic policies and human capital development to effectively address inequality. The study contributes to the discourse on Islamic economic instruments and offers policy insights for leveraging zakat as part of a broader socio-economic strategy.